In vivo Visualization of Collagen Transdermal Absorption by Second-Harmonic Generation and Two-Photon Excited Fluorescence Microscopy - Sun, Yanan; Li, Lishuang; Ma, Shuhua; He, Gaiying; Yang, Weifeng; Wang, Yi (Frontiers in Chemistry, 2022)
The transdermal administration of collagen is an important method used for wound healing and skin regeneration. However, due to the limitations of previous approaches, the process and degree of collagen transdermal absorption could only be quantitatively and qualitatively evaluated in vitro. In the present study, we introduced a novel approach that combines second-harmonic generation with two-photon excited fluorescence to visualize the dynamics of collagen transdermal absorption in vivo. High-resolution images showed that exogenous recombinant human collagen permeated the epidermis through hair follicles and sebaceous glands, reached the dermis, and formed reticular structures in real time. We also validated these findings through traditional in vitro skin scanning and histological examination. Thus, our approach provides a reliable measurement for real-time evaluation of collagen absorption and treatment effects in vivo.